Variação genética, dinâmica populacional e adaptação de xylocopa grisescens lepeletier em paisagens semiáridas degradadas - Brasil, Sandara Nadja Rodrigues (2021)
One of the main goals in Conservation Biology is to understand the habitat effects on a deem species or species group. Despite global concerns about the negative effects of desertification on biodiversity, studies that address these effects considering the genetic conservation of populations are still limited. Globally, arid and semi-arid environments have a unique characteristic regarding the genetic conservation of their populations due to the fact that at the same time, they exhibit food, nesting, and reproductive scarcity; they also provide adaptive components to certain species. In Brazil, the area most susceptible to desertification is found in the semi-arid and subhumid region of the Northeast, which has a history of continuous degradation over many decades until the present day. Considering that highly heterogeneous habitats play a considerable role in achieving genetic differentiation and local adaptation and that anthropogenic degradation negatively affects the genetic diversity of populations, it is essential to understand how these environments shaped the populations genetically. Environments. Also, due to the long period in which the Brazilian semi-arid region suffered from the degradation of its landscapes, it is important to access the demographic history of populations in order to identify what changes (division, merger, bottlenecks, or expansion) have occurred in these populations over time. Therefore, here we investigate how the extremely degraded landscapes of the Brazilian semiarid region, here described as areas susceptible to desertification (ASD), have been affecting the genetic variability, population dynamics, and adaptation of an important pollinator of the semi-arid northeast, the bee Xylocopa grisescens. For this purpose, we collected 80 females of X. grisescens at eight sampling sites in the State of Ceará, in Northeastern Brazil, covering distances of up to 300 km. We used RADseq(Restriction site association DNA sequencing) to identify 83,127 SNPs (Single Nucleotide Polymorphism). We access genetic diversity, genetic structure, demographic history, gene flow, and possible barriers to gene flow in populations through molecular genetics, bioinformatics, and statistical analysis techniques. We detected a low amount of genetic diversity and differentiation between different populations, although the distribution of this genetic diversity is relatively heterogeneous across sites. Inferences about the demographic history of X. grisescens revealed the current effective population size of about ~5,000 individuals and the population reduction for about ~100 to ~150 years. X. grisescens maintained a viable population size to keep this species thriving in such degraded habitat. Also, the results on gene flow and adaptation revealed that populations are more adapted to precipitation metrics than temperature or altitude and that gene flow is not restricted probably due to the high concentration of pastures and agriculture in the semi-arid region of Brazil, which favors the flowering of preferred native plant species and crops X. grisescens. Our data suggest that despite the ongoing desertification process greatly impacting the Brazilian semiarid region, these ecological changes are not genetically affecting the genetic variability of X. grisescens.